Pregnane X receptor mediates sorafenib resistance in advanced hepatocellular carcinoma - Feng, Fan; Jiang, Qiyu; Cao, Shuang; Cao, Yu; Li, Ruisheng; Shen, Lijun; Zhu, Hua; Wang, Tao; Sun, Lijun; Liang, Erguang; Sun, Huiwei; Chai, Yantao; et al. (Biochimica et biophysica acta. General subjects, 2018)
Kinase inhibitor sorafenib is the most widely used drug for advanced HCC clinical treatment nowadays. However, sorafenib administration is only effective for a small portion of HCC patients, and the majority develop sorafenib-resistance during treatment. Thus, it is urgent to discover the endogenous mechanism and identify new pharmaceutical targets of sorafenib-resistance. Pregnane X receptor (PXR) was detected by immunohistochemistry and quantitative PCR. GST-pull down and LC-MS/MS was used to detect the interaction of PXR and Sorafenib. To test the properties of HCC tumor growth and metastasis, in vivo tumor explant model, FACS, trans-well assay, cell-survival inhibitory assay and Western blot were performed. In terms of mechanistic study, additional assays such as ChIP and luciferase reporter gene assay were applied. In the present work, we found high PXR level in clinical specimens is related to the poor prognosis of Sorafenib treated patients. By the mechanistic studies, we show that sorafenib binds to PXR and activates PXR pathway, and by which HCC cells develop sorafenib-resistance via activating. Moreover, PXR overexpression helps HCC cells to persist to sorafenib treatment. This study reports the endogenous sorafenib-resistance mechanism in HCC cells, which offers an opportunity to design new therapeutic approaches for HCC treatment. PXR mediates sorafenib-resistance in HCC cells and targeting PXR can be a useful approach to facilitate HCC treatment. [Display omitted] •HCC cells develop sorafenib-resistance by activated PXR.•High level of PXR in clinical specimens is related to poor of sorafenib treament.•PXR may be a novel target to over come sorafenib-resistance.